THEORETICAL ASPECTS OF CORPORATE COMMUNICATION AND ITS COMPONENTS - Edi Luketa (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Corporate communication in its essence is the concept of comprehensive communication of a business organization with stakeholders. Given its importance in the implementation of modern business trends and processes, it has become an integral element in all business organizations and one of the key management functions in corporate business systems. The aim of this paper was to gain an overview of the most relevant scientific theories of corporate communication and its basic components. Despite the scientists who have defi ned it by numerous theories, due to its comprehensiveness, to this day, no agreement has been reached by the scientifi c community on a basic scientifi c defi nition. The added value of this paper is an insight into the theories of the most eminent scientific authorities for the purpose of reviewing the comprehensiveness of the field and considering further scientific research. Putting the available theories in the context of the speed of business and technological changes to which business organizations must adapt, it can be concluded that corporate communication will follow the processes of adaptation which will certainly result in new scientific interpretations and thus make it difficult for the scientific community to agree on basic scientific theory.